Pemberian ASI terhadap Komposisi Tubuh pada Bayi Prematur: A Systematic Review: Breastfeeding on Body Composition in Premature Infants: A Systematic Review - Dzulkifli, Achmad; Nadhiroh, Siti Rahayu; Syahdana, Achidah Nur (Universitas Airlangga, 2024)
Background: Premature newborns have a higher susceptibility to metabolic syndrome and cognitive impairment compared to infants born at full term. Breast-feeding is advised as a natural source of nutrition for premature newborns and as a cost-effective approach to decrease illness and financial strain. Assessing preterm children's growth and body composition upon leaving the hospital is crucial and requires great attention due to its sensitivity and significance in determining future care. Objectives: This study aimed to compare the body composition of preterm infants who were fed breast milk against formula. Methods: This study employed a systematic survey approach, which involved the use of fifteen exploratory diaries covering the period from 2013 to 2023. The search terms employed were